The Effect of Sintering Duration Time and Cooling Condition on High TcPhase of i-Sr-Ca-Cu-O Superconductor - Makadsi, M.; Al-Ani, S.; Muter, S. (Iraqi Journal of Science, 2025)
High-Tc ceramic superconductor compound Bi2Sr2Ca2Cu3O10 has been prepared by solid state reaction technique. Three sets of samples were prepared in order to study the effect of cooling conditions after sintering on superconductors, the first set of samples were (furnace cooled samples), the second set was (quenched in air), while the third set was (quenched in liquid nitrogeFour sintering duration time (50, 100, 150 and 200h) were used to determine the effective time that needed to increase the volume fraction of the high-Tc phase. It was found that the quenched in air samples show high- Tc and sharp superconducting transition, but the quenched in liquid nitrogen samples show low –Tc. The higher Tc obtained was 110 K and the proper sintering time was 150h. The x-ray diffraction pattern was used to identify the phases and the value of lattice parameters (a, b, and c).